Recombinant human fibroblast growth factor 7 obtained from stable Chinese hamster ovary cells enhances wound healing - 김영식 (The Graduate School, Ajou University, 2024)
Wounds can occur due to various causes such as physical trauma or infection. To facilitate the healing of such wounds, it is necessary to apply active treatments utilizing growth factors like FGF7 or appropriate wound dressings combined with growth factors. FGF7, produced in large quantities from CHO cells, and animal models treated with FGF7 and collagen patches have showed effective promotion of wound healing. CHAPTER I: Fibroblast growth factor 7 (FGF7) is recognized as one of the growth factors promoting wound healing. However, study on its mass production remains scarce, particularly regarding its feasibility in Chinese hamster ovary (CHO) cells. Therefore, this study aimed to evaluate the potential of CHO cells for large-scale production of recombinant FGF7 and assess its efficacy in wound healing model. The FGF7 gene was stably transfected into CHO cells. A single clone was selected from the transfected CHO cell population using semi-solid method. The selected single clone achieved a productivity of 102.8 ± 6.8 mg/mL (9-day culture) through MTX amplification, screening of culture media, and optimization of culture temperature. The produced FGF7 had a molecular weight of 20-30 kDa due to oxidation, deamidation, and glycosylation, with an isoelectric point ranging from 4.61 to 7.34. The glycosylated FGF7 exhibited a complex N-glycan pattern with over 14 different types of glycans attached, and its biological activity showed a slightly higher activity of 7.49 ng/mL compared to the activity of E. coli-derived FGF7, which was 7.74 ng/mL. In conclusion, this study showed that the glycosylated FGF7 produced in CHO cells exhibits stable large-scale production. In summary, this study showed the capacity for FGF7 mass production in CHO cells and its potential as a biopharmaceutical. CHAPTER II: To facilitate rapid recovery of wound sites, the application of appropriate wound dressings and the supply of external growth factors such as FGF7, which is secreted during wound healing phase, can actively promote wound healing. The wound healing efficacy of produced N-glycosylated FGF7 was evaluated in animals on days 7 and 14 post-treatment using collagen patches (CP), FGF7 alone, and CP combined with FGF7 (CP+FGF7), with an untreated group serving as the control. Notably, wound closure was most effective in the CP+FGF7 group. Particularly, on day 7 post-treatment, both CP+FGF7 and FGF7-alone groups exhibited the highest expression of hydroxyproline, fibroblast growth factor, vascular endothelial growth factor, and transforming growth factor β. Histological assessment by H&E staining revealed a parallel trend in epidermalization with hydroxyproline levels. Additionally, CP+FGF7 and FGF7-alone groups demonstrated notable vascularization on days 7 and 14. Therefore, this study has shown that using wound dressings in combination with FGF7 promotes wound healing more effectively than using wound dressings alone. In conclusion, FGF7 can be reliably mass-produced from CHO cells, and when used in combination with collagen patches, it significantly enhanced wound healing in animal models. Therefore, FGF7 production in CHO showed potential for commercialization due to its ability for large-scale production and its potential as a biopharmaceutical. Keywords: MTX amplification, culture media screening, recombinant FGF7, CHO, N- glycosylated, growth factors, wound healing, dressing, collagen patches
학위논문(박사)--분자과학기술학과,2024. 8
Keywords: CHO; dressing; recombinant FGF7; wound healing